2008
DOI: 10.1179/136485908x311768
|View full text |Cite
|
Sign up to set email alerts
|

School-based health education for the control of soil-transmitted helminthiases in Kanchanaburi province, Thailand

Abstract: Soil-transmitted helminthiases are major parasitic diseases that cause health problems world-wide. School-based health education is one of several basic interventions currently recommended by the World Health Organization for the control of these infections. A 3-year programme of health education for the control of soil-transmitted helminths (STH) has recently been completed in four primary schools in the Hauykayeng subdistrict of Thong Pha Phum district, in the Kanchanaburi province of Thailand. Overall, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 4 publications
3
17
0
1
Order By: Relevance
“…Hookworms were the most common helminths found in the schoolchildren, which is consistent with previous reports conducted in southern Thailand [ 15 17 ]. However, the observed hookworm infection prevalence of 10.7% was lower than reports from a similar study in southern Thailand, which reported a prevalence of 21.1% in 2002 [ 17 ], and a national survey, which reported a prevalence of 15.8% in 2009 [ 15 ]. The lower hookworm infection prevalence in the present study may be due to differences in urbanization, improved knowledge of personal hygiene, and improved environmental sanitation, for example, clean and safe water supply, and effective human and animal waste disposal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hookworms were the most common helminths found in the schoolchildren, which is consistent with previous reports conducted in southern Thailand [ 15 17 ]. However, the observed hookworm infection prevalence of 10.7% was lower than reports from a similar study in southern Thailand, which reported a prevalence of 21.1% in 2002 [ 17 ], and a national survey, which reported a prevalence of 15.8% in 2009 [ 15 ]. The lower hookworm infection prevalence in the present study may be due to differences in urbanization, improved knowledge of personal hygiene, and improved environmental sanitation, for example, clean and safe water supply, and effective human and animal waste disposal.…”
Section: Discussionsupporting
confidence: 92%
“…The sample size was determined using the single proportion population formula: where p = prevalence of intestinal parasites from a previous study, d = margin of error, and Z = the value from a standard normal distribution corresponding to the desired confidence level, which equals 1.96 for a 95% CI. This formula was calculated based on a prevalence rate of 24.1% from a previous study [ 17 ], with a margin of error of 0.05 and a confidence level of 95%. The appropriate sample size was determined to be 286.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five studies have previously investigated the efficacy or effectiveness of a health education intervention on STH prevalence or re-infection rates, with one study showing the benefits of such intervention on prevalence [21][25]. They, however, do not provide an adequate appreciation of the impact of a health education intervention because of methodological limitations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This recognition has served as the basis for school-based health prevention curricula across Africa [11–13], Asia [14, 15], and Latin America [16, 17] including family planning programs [18, 19], nutrition programs [2022], and tobacco-prevention campaigns [23, 24]. …”
Section: Introductionmentioning
confidence: 99%